2009
DOI: 10.1097/bpb.0b013e32832f724c
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of Ethibloc injection in aneurysmal bone cysts

Abstract: The aim of this study is to assess the long-term results of Ethibloc injection in aneurysmal bone cysts (ABC). Thirty-three patients with ABC were treated with computed tomography-guided percutaneous injection of Ethibloc into the cyst cavity. Twenty-two patients had Ethibloc injection as primary treatment and 11 patients had presented to us with recurrence after previous procedures including steroid injection, bone marrow injection, curettage bone grafting and various other surgical procedures. The mean follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…Intralesional injections of calcitonin with steroids have proved to be safe and effective in regression of ABC lesions [16]. Doxycycline, Ethibloc® (Ethicon, Norderstedt, Germany), which is a mixture of zein, oleum papaveris and propylene glycol, and an aqueous solution of calcium sulfate have proved to be successful alternative treatments with low recurrence rates [17,18]. Radiotherapy is generally contraindicated secondary to adverse effects of radiation on growth plates and potential for future tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Intralesional injections of calcitonin with steroids have proved to be safe and effective in regression of ABC lesions [16]. Doxycycline, Ethibloc® (Ethicon, Norderstedt, Germany), which is a mixture of zein, oleum papaveris and propylene glycol, and an aqueous solution of calcium sulfate have proved to be successful alternative treatments with low recurrence rates [17,18]. Radiotherapy is generally contraindicated secondary to adverse effects of radiation on growth plates and potential for future tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Osseous lesions in cervical vertebral bodies supplied by arterial branches of the vertebral arteries has also been described by Turowski et al [21]. A recent study of long-term followup of Ethibloc® injection concluded that the technique is minimally invasive and effective, but is not recommended for ABC of the spine [22]. Other techniques have been described for treatment of cervical ABC, such as percutaneous intra-lesional injection of calcitonin and methylprednisolone [23,24] or primary surgical management for deep lesions with extensive bone destruction [25].…”
mentioning
confidence: 86%
“…In a study by Gibbs et al (32), the cortex was cleaned with a burr drill in addition to the curettage and bone grafting, and the recurrence rate was reported as 10%, and patients with open physes were reported as the greatest risk factor for this recurrence. George et al (33), who injected ethibloc into the cyst, published a successful long follow-up series with 58% complete recovery, 35.5% partial recovery, and 6.5% recurrence. In addition to the curettage and bone grafting, they also used argon beam coagulation as an adjuvant, and reported that they did not found any recurrence (34).…”
Section: Discussionmentioning
confidence: 99%